Protocolised reduction of non-resuscitation fluids versus usual care in patients with septic shock (REDUSE): a protocol for a multicentre feasibility trial. Issue 2 (28th February 2023) - Lindén, Anja; Fisher, Jane; Lilja, Gisela; Olsen, Markus Harboe; Sjövall, Fredrik; Jungner, Mårten; Spångfors, Martin; Samuelsson, Line; Oras, Jonatan; Linder, Adam; Unden, Johan; Kander, T; et al.
Abstract : Introduction: Administration of large volumes of fluids is associated with poor outcome in septic shock. Recent data suggest that non-resuscitation fluids are the major source of fluids in the intensive care unit (ICU) patients suffering from septic shock. The present trial is designed to test the hypothesis that a protocol targeting this source of fluids can reduce fluid administration compared with usual care. Methods and analysis: The design will be a multicentre, randomised, feasibility trial. Adult patients admitted to ICUs with septic shock will be randomised within 12 hours of admission to receive non-resuscitation fluids either according to a restrictive protocol or to receive usual care. The healthcare providers involved in the care of participants will not be blinded. The participants, outcome assessors at the 6-month follow-up and statisticians will be blinded. Primary outcome will be litres of fluids administered within 3 days of randomisation. Secondary outcomes will be proportion of randomised participants with outcome data on all-cause mortality; days alive and free of mechanical ventilation within 90 days of inclusion; any acute kidney injury and ischaemic events in the ICU (cerebral, cardiac, intestinal or limb ischaemia); proportion of surviving randomised patients who were assessed by European Quality of Life 5-Dimensions 5-Level questionnaire and Montreal Cognitive Assessment; proportion of all eligible patients who were randomised and proportion of participants experiencing at least one protocol violation. Ethics and dissemination: Ethics approval has been obtained in Sweden. Results of the primary and secondary outcomes will be submitted for publication in a peer-reviewed journal. Trial registration number: NCT05249088 .